Experimental Investigations of the Stress and Strain State of Continuous Reinforced Concrete Beams Under the Action of Low-Cyclic Repetitive and Alternating Loads - Masiuk, Grigoriy; Yushchuk, Oleksandr; Paschenko, Andrii (International Journal of Engineering and Technology, 2018)
The article is devoted to the experimental studies of the stress and strain state of the two-pass reinforced concrete beams under the influence of low-cyclic repeated and alternating loads. Based on the results of experimental studies, the effect of low-cyclic repeated and alternating loads on the change of the stress and strain state of continuous reinforced concrete beams has been established. In the course of testing the sample, it was found that the stress and strain state of the beams under the action of the above mentioned loads is significantly different from the stress and strain state of the beams under the action of nonalternating static loads, namely, the decrease of the bearing capacity, the increase of the deflections and the width of the cracking. All this is due to the change in the physical and mechanical properties of concrete in response to the above-mentioned loads on experimental. Â Â